Tecnologia ADS-B no Linux, uma implementação de decodificação e persistência de mensagens - Carvalho, Sidartha Azevedo Lobo de (2012)
This work is a literature mapping on air monitoring technologies, with focus on the Automatic Dependent Surveillance - Broadcast (ADS-B) technology and shows projects of ADS-B technology deployment in several countries. It explains a macro project of decoding ADS-B messages, creating the infrastructure necessary to interconnect various access points with ADS-B receivers and communication with a central database for sharing information of nodes. It also demonstrates how it should be made to interpret the messages encoded by the Mode-S and implements an application that performs the detection process of the types of ADS-B messages and how to extract the important information of the messages.